Climate Innovation - The Case of the Central German Chemical Industry - Wilfried Ehrenfeld (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2012)
In this article, we describe the results of a multiple case study on the indirect corporate innovation impact of climate change in the Central German chemical industry. We investigate the demands imposed on enterprises in this context as well as the sources, outcomes and determining factors in the innovative process at the corporate level. We argue that climate change drives corporate innovations through various channels. A main finding is that rising energy prices were a key driver for incremental energy efficiency innovations in the enterprises' production processes. For product innovation, customer requests were a main driver, though often these requests are not directly related to climate issues. The introduction or extension of environmental and energy management systems as well as the certification of these are the most common forms of organizational innovations. For marketing purposes, the topic of climate change was hardly utilized so far. As the most important determinants for corporate climate innovations, corporate structure and flexibility of the product portfolio, political asymmetry regarding environmental regulation and governmental funding were identified. – – In diesem Artikel beschreiben wir die Ergebnisse einer multiplen Fallstudie zu den indirekten betrieblichen Innovationswirkungen des Klimawandels in der mitteldeutschen Chemieindustrie. Wir untersuchen die neuen Anforderungen an Unternehmen in diesem Zusammenhang ebenso wie Quellen, Ergebnisse und bestimmende Faktoren im Innovationsprozess auf Unternehmensebene. Wir gelangen dabei zu der Auffassung, dass der Klimawandel betriebliche Innovationen über verschiedene Kanäle vorantreibt. Ein Hauptergebnis dieser Studie ist, dass steigende Energiepreise ein wesentlicher Treiber für inkrementelle Energieeffizienzinnovationen in den Fertigungsprozessen von Unternehmen sind. Für Produktinnovationen waren Kundenwünsche ein wichtiger Anlass, wenn auch diese Anfragen oft nicht direkt mit Fragen des Klimas in Verbindung stehen. Die Einführung oder Erweiterung von Umwelt- bzw. Energie-Management-Systemen sowie die Zertifizierung dieser sind die häufigsten Formen von organisatorischen Innovationen. Für Zwecke des Marketings war das Thema Klimawandel bislang noch relativ unbedeutend. Als die wichtigsten Determinanten für betriebliche Klimainnovationen wurden Unternehmensstruktur und Flexibilität des Produktportfolios, politische Asymmetrie in Bezug auf Umweltregulierung sowie staatliche Fördermittel identifiziert.
urn:nbn:de:101:1-201206114383
Keywords: Q55; O33; O38; Q54; O31; 330; climate change; innovation; chemical industry; Central Germany; Klimawandel; Innovation; Chemische Industrie; Mitteldeutschland